CEO School - Shekshnia, Stanislav; Kravchenko, Kirill; Williams, Elin (Ascent Audio, 2021)
This book focuses on what makes a successful CEO and the paths to becoming one in today's global economy. Chapters in the book include insights by twenty top CEOs-one from each G20 country-gathered from an extensive global qualitative research project. Through seven easy-to-digest "master classes" that demystify the role of the twenty-first-century CEO, the authors present their findings in an accessible, conversational style that serves as a step-by-step guide for those who aspire to become CEOs and develop essential character traits, experience, and skills required of the role.